노인 암환자의 건강정보 이해능력을 반영한 항암화학요법 자기관리 프로그램 개발 및 평가 - 김윤선; 태영숙; 정귀임; Kim, Yoon Sun; Tae, Young Sook; Jung, Kwuy-Im (Journal of Korean Academy of Nursing, 2019)
Purpose: This study aimed to develop and evaluate the effectiveness of an adapted health literacy self-management intervention for elderly cancer patients undergoing chemotherapy. Methods: The intervention in this study was systematically developed through the six stages of Intervention Mapping Protocol and was based on Fransen et al's causal pathway model. A quasi-experimental trial was conducted on a total of 52 elderly patients (26 in an experimental group and 26 in a control group) undergoing chemotherapy in Korea. The intervention consisted of seven sessions over 5 weeks. The experimental tool for this study was an adapted health literacy self-management intervention, which was designed to promote a reduction in the symptom experience and distress of elderly cancer patients through the promotion of self-management behavior. To develop efficient educational materials, the participants' health literacy was measured. To educate participants, clear communication and the teach-back method were used. In addition, for the improvement of self-efficacy, four sources were utilized. For the promotion of self-management behavior, five self-management skills were strengthened. Data were collected before and after the intervention from June 4 to September 14, 2018. The data were analyzed with SPSS/WIN 21.0. Results: Following the intervention, self-management knowledge and behavior and, self-efficacy significantly improved in experimental group. Symptom experience and distress decreased in the experimental group compared to the control group. Conclusion: The self-management intervention presented in this study was found to be effective in increasing self-management knowledge and behavior and, self-efficacy, and ultimately in reducing symptom experience and distress for elderly patients undergoing chemotherapy.